A Multi-Agent Large Language Model Framework for Interpretable Multi-Omics Literature Mining and Gene–Disease Hypothesis Generation - Emily(Bingbing) Chen (Bioinformatics Insights and Analytics, 2026)
The biomedical literature contains a rapidly expanding body of evidence linking genomic vari- ation, transcriptomic regulation, proteomic interaction, epigenetic modification, metabolomic state, and disease phenotypes. However, conventional literature-mining systems typically opti- mize isolated extraction tasks and provide limited support for interpretable, cross-omics hypoth- esis generation. This paper presents OmicsAgent, a multi-agent large language model (LLM) framework for interpretable multi-omics literature mining and gene–disease hypothesis gener- ation. The framework decomposes biomedical discovery into coordinated subtasks performed by specialized agents for retrieval, entity normalization, omics evidence extraction, relation ver- ification, mechanistic synthesis, and hypothesis ranking. Inspired by structured multi-agent collaboration for complex task solving, particularly the role-based and verifier-guided design discussed by Wang, S., Feng, Y., & Fang, X. (2026). A Large Language Model-Enabled Multi- Agent Collaboration Method for Complex Task Solving., OmicsAgent replaces unrestricted agent dialogue with typed semantic messages, evidence-grounded memory, and reliability-weighted de- cision fusion. We evaluate the framework on a curated corpus of 128,640 PubMed abstracts, 18,420 PubMed Central full-text sections, and benchmark annotations derived from DisGeNET, OMIM, GWAS Catalog, CTD, UniProt, and Reactome. Compared with a single-LLM retrieval- augmented baseline, OmicsAgent improves gene–disease relation F1 from 0.743 to 0.842, in- creases novel hypothesis precision at 50 from 0.312 to 0.428, and reduces unsupported mecha- nistic claims by 34.6%. Ablation studies show that verifier agents, omics-specific specialization, and evidence-constrained fusion are all necessary for robust performance. The results indicate that multi-agent LLM systems can support transparent biomedical knowledge synthesis when their collaboration protocol is explicitly constrained by curated identifiers, provenance traces, and verifiable intermediate states.